New Assay for Measuring Binding of Platelet Glycoprotein IIb/IIIa to Unpurified von Willebrand Factor - Veyradier, Agnès; Jumilly, Anne-Lise; Ribba, Anne-Sophie; Obert, Bernadette; Houllier, Anne; Meyer, Dominique; Girma, Jean-Pierre (Thrombosis and Haemostasis, 1999)
Among the numerous variants of vWD, no patient with an abnormal vWF binding to GPIIb/IIIa has been described to date. To search for such potential variants, we developed a two-site assay for measuring the binding of purified GPIIb/IIIa to vWF in biological fluids and we used it to study a large series of plasmas from various types of von Willebrand disease (vWD) and recombinant vWF (rvWF).vWF in plasma or rvWF in culture medium was immobilized onto anti-vWF monoclonal antibodies (MoAb)-coated wells of microtiter plates. After incubation with either unlabeled GPIIb/IIIa and a 125I-anti-GPIIb/IIIa MoAb or 125I-GPIIb/IIIa, binding curves and binding isotherms were respectively established. Normal pool plasma and wild-type rvWF were used as reference samples. We tested plasmas from 85 normal subjects, 115 patients with different types of vWD (64 type 1, 2 type 3, 9 type 2A, 4 type 2M, 16 type 2B, 15 type 2N, 3 type IID and 2 acquired forms) and 50 patients with various bleeding disorders. Four mutated rvWF with 2A (Glu875Lys and Pro885Ser) or 2B (Dupl.Met540 and Val551Phe) substitutions and one rvWF mutated in the RGD domain of the C-terminal part of vWF-subunit (Asp1746Gly) were also studied.Among the various samples tested, only rvWF Asp1746Gly had no affinity for GPIIb/IIIa. In contrast, GPIIb/IIIa similarly bound to the other vWF, independently of the proteic environment, the factor VIII level, the degree of multimerization or the mutation of vWF. Our results indicate that subjects with an abnormal vWF binding to GPIIb/IIIa are probably rare and difficult to target for a specific screening.